Development of Efficient Essential Medicine Inventory Control Model Using ABC, VEN, EOQ, and ROP Methods - Mellani Pratiwi; Rina Mutiara; Aprilita Rina Yanti (Harmony Management: International Journal of Management Science and Business, 2026)
The management of essential drug inventory is a strategic component of hospital pharmaceutical services because it directly influences service continuity, cost efficiency, and the overall quality of healthcare delivery. Poor inventory control can result in excessive stock accumulation, increased risk of drug expiration, inefficient budget utilization, and potential drug shortages that may compromise patient care. This study aims to evaluate the effectiveness of essential drug inventory control at Pekerja General Hospital by applying the ABC-VEN, Economic Order Quantity (EOQ), and Reorder Point (ROP) methods. It also examines differences in inventory management efficiency between 2024 and 2025 based on inventory value, cost of goods sold (COGS), and Inventory Turnover Ratio (ITOR). A mixed-methods approach with a sequential explanatory design was used. Quantitative analysis involved a paired sample t-test comparing inventory data from 2024–2025, while qualitative data were collected through in-depth interviews and analyzed thematically using NVivo. The findings reveal a significant improvement in inventory management in 2025 (p < 0.05), reflected in reduced inventory value and COGS, along with an increased ITOR. However, the implementation of ABC-VEN, EOQ, and ROP methods has not been fully integrated, and challenges such as limited human resources and procurement bureaucracy persist.In conclusion, although inventory control became more efficient in 2025, further integration of inventory methods and strengthening of human resource capacity are necessary to ensure sustainable improvements.